TEST OF A NET DOME FRAGMENT (Collection of scientific works «Modern structures of metal and wood», 2021)
A geodesic or net dome, also known as a Fuller’s dome, is a spherical structure. Geodesic  domes  are  well  receptive  to  asymmetric  loads,  especially  snow  and  wind,  have  high aerodynamics, increased rigidity and stability. It should be noted that the larger the diameter of the sphere, the greater its bearing capacity, and the strength of such dome slightly depends on the building materials used. With significant advantages, the design and construction of wooden net domes has not become widespread. The fact is that net domes are spatial structures with a large number of elements, which accordingly entails a large number of nodes. The elements of the dome are connected with dowels, wet film gauge, bolts, wood screws, staples, screws, nails. Adhesive connections on washers  are  used,  also  steel  clamps,  straps,  overlays  are  applied.  However,  they  all  have disadvantages, the scope of each connector is different, and their cost is often comparable to the cost of the dome elements. We offer a universal connector for connecting dome parts at any angle. As a result  of  introduction  of  such  technical  decision  of  knot,  we  receive  essential  simplification  of  a design, reduction of quantity of components, at the same time with increase of its manufacturability. To study the operation of the joint of wooden glue-board elements of the dome with the use of a universal connector, its experimental studies were carried out.  The purpose of the study: to study the actual operation of the connection of wooden parts of the dome with a universal connector in the form of rotating fasteners that rotate freely on the draw bolt, to assess its strength and deformability, to assess the possibility of using such a connection in the design of spatial structures. To solve the tasks, a full-scale fragment of the dome was tested, which includes characteristic nodes with rigid adjacency of elements to each other.